2024
DOI: 10.3389/fcell.2024.1289335
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and its current progress in gastric cancer

Zhenqi Yue,
Yiwu Yuan,
Qi Zhou
et al.

Abstract: Gastric Cancer (GC) is a prevalent malignancy within the digestive tract, ranking as the fifth most common malignant tumor worldwide. It is characterized by clinical features such as a tendency for metastasis and an unfavorable prognosis. Ferroptosis, a recently identified form of cell death, represents a novel mode of cellular demise that diverges from the traditional concepts of necrosis and apoptosis. Numerous studies have found that ferroptosis plays a significant role in the proliferation, metastasis, dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“… Ning et al (2024) found that some plant extracts, exosomes, and plasmids exhibited the repair of radiation-induced hematopoietic and skin damage by inhibiting ferroptosis; Melatonin promoted the binding of Nrf2 and pyruvate kinase isoenzyme M2 (PKM2), which reduced iron concentration and inhibited ferroptosis to alleviate radiation-induced hippocampal neuronal death. Yue et al (2024) summarized that various anti-tumor drugs such as cisplatin, paclitaxel, capecitabine, apatinib and artemisinin could induce ferroptosis in gastric cancer (GC) cells. And even dexmedetomidine (DEX), levobupivacaine and other local anesthetics had potential value in the treatment of GC due to their ability in regulating ferroptosis and inhibiting GC ell proliferation.…”
Section: Clinical Researches Progress Of Targeting Ferroptosis In The...mentioning
confidence: 99%
“… Ning et al (2024) found that some plant extracts, exosomes, and plasmids exhibited the repair of radiation-induced hematopoietic and skin damage by inhibiting ferroptosis; Melatonin promoted the binding of Nrf2 and pyruvate kinase isoenzyme M2 (PKM2), which reduced iron concentration and inhibited ferroptosis to alleviate radiation-induced hippocampal neuronal death. Yue et al (2024) summarized that various anti-tumor drugs such as cisplatin, paclitaxel, capecitabine, apatinib and artemisinin could induce ferroptosis in gastric cancer (GC) cells. And even dexmedetomidine (DEX), levobupivacaine and other local anesthetics had potential value in the treatment of GC due to their ability in regulating ferroptosis and inhibiting GC ell proliferation.…”
Section: Clinical Researches Progress Of Targeting Ferroptosis In The...mentioning
confidence: 99%
“…Ferroptosis, a non-apoptotic type of RCD, exhibiting distinct morphological, biochemical, and genetic characteristics compared to other types of cell death, is modulated by multiple cellular metabolic processes such as iron handling, glycolipid metabolism, and redox homeostasis, along with various signaling pathways associated with disease progression [ 21 , 22 ]. Ferroptosis is characterized by the existence of diminished mitochondria and decreased mitochondrial cristae [ 23 ]. This mechanistic characteristic sets ferroptosis apart from other modes of RCD, which are governed by specific proteins that execute cell death [ 24 ].…”
Section: Introductionmentioning
confidence: 99%